Geothermal power plant layouts with water absorption and reinjection of H2S and CO2 in fields with a high content of non-condensable gases - Giovanni Manente; Andrea Lazzaretto; Alessio Bardi; Marco Paci (Elsevier, 2019)
The reinjection of non-condensable gases (NCG) back to the geothermal reservoir has recently proved to be an effective emission abatement method in Iceland, yet it would raise new challenges when applied to geothermal fields with a much higher NCG content and different reservoir’s rock composition like the Italian fields. The features of the surface equipment to implement gas reinjection are rarely reported in the literature, being the attention mostly focused on the subsurface reservoir. To fill this gap, this study examines the integration of the water absorption and reinjection equipment in dry steam and flash steam geothermal power plants fed by steam with a high NCG content (8%). Three novel plant layouts are proposed, modelled and analysed which include a packed absorption column where H2S and CO2 are absorbed in water at high pressure. The study searches for those conditions ensuring an overall H2S abatement similar to that achieved by state-of-the-art emission abatement methods (e.g., AMIS) and, at the same time, enabling a significant capture of the CO2 contained in the geothermal steam, which is currently unabated. The results show that, with minimum modifications to the original plant layout, an overall H2S abatement of 86.5% and CO2 abatement of 47% are attainable. This is obtained using a column pressure of 36 bar, a water supply of 100 ton/hr, and coping with a net power output reduction of 6% and a moderate cost of the added equipment estimated equal to 1.0–2.2 M€.